Haemophagocytic lymphohistiocytosis triggered by cytomegalovirus reactivation in an immunosuppressed patient with pauci-immune glomerulonephritis - Léa Docquier; Ishak Beklevic; Serge Treille de Grandseigne; Benoit Guillaume; Aline Pourcelet (European Journal of Case Reports in Internal Medicine, 2024)
We report on a 67-year-old male patient admitted to the Internal Medicine department for fever, joint pain and exertional dyspnoea. Two months before his admission, the patient had been diagnosed with pauci-immune necrotising glomerulonephritis, for which he had been treated with rituximab and corticosteroids. Upon admission the patient was stable, but within a few hours he became unstable as liver failure and acute cytopaenia occurred. Blood investigations revealed cytopaenia, altered coagulation tests, high ferritin, triglycerides, lactate dehydrogenase and C-reactive protein levels, and severe cytocholestasis. A liver echography was normal. The patient had been transferred to the intensive care unit to receive supportive support when the cytomegalovirus polymerase chain reaction (CMV-PCR) test came back positive. The diagnosis of haemophagocytic lymphohistiocytosis associated with a CMV infection and/or reactivation in an immunosuppressed patient was made. Specific treatment was administrated, along with symptomatic treatment. The patient clinically improved during hospitalisation with complete resolution of symptoms.